2009
DOI: 10.1115/1.4000258
|View full text |Cite
|
Sign up to set email alerts
|

2D Numerical Simulations of Blade-Vortex Interaction in a Darrieus Turbine

Abstract: The aim of this work is to provide a detailed two-dimensional numerical analysis of the physical phenomena occurring during dynamic stall of a Darrieus wind turbine. The flow is particularly complex because as the turbine rotates, the incidence angle and the blade Reynolds number vary, causing unsteady effects in the flow field. At low tip speed ratio, a deep dynamic stall occurs on blades, leading to large hysteresis lift and drag loops (primary effects). On the other hand, high tip speed ratio corresponds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…Ferreira et al [22] use detached eddy simulation (DES) focusing on 2D dynamic stall and validate the results with particle image velocimetry data. It is to be noted that in the Darrieus-type VAWT, a cyclic phenomenon of dynamic stall and vortex separation is present [8,22,23]. Amet et al [23] provided a detailed numerical analysis of the physical phenomena that occur during dynamic stall where the compressible RANS κ − ω model and multi-block mesh structure were used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferreira et al [22] use detached eddy simulation (DES) focusing on 2D dynamic stall and validate the results with particle image velocimetry data. It is to be noted that in the Darrieus-type VAWT, a cyclic phenomenon of dynamic stall and vortex separation is present [8,22,23]. Amet et al [23] provided a detailed numerical analysis of the physical phenomena that occur during dynamic stall where the compressible RANS κ − ω model and multi-block mesh structure were used.…”
Section: Introductionmentioning
confidence: 99%
“…It is to be noted that in the Darrieus-type VAWT, a cyclic phenomenon of dynamic stall and vortex separation is present [8,22,23]. Amet et al [23] provided a detailed numerical analysis of the physical phenomena that occur during dynamic stall where the compressible RANS κ − ω model and multi-block mesh structure were used. Furthermore, studies of dynamic stall show that the Shear Stress Transport (SST) κ − ω turbulence model performs better than the κ − ω model, as reported by Ekaterinaris and Platzer [24] and Qian et al [25].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang Hongming et al present numerical simulation of blade channel vortex in a low head Francis turbine using OpenFoam code, the simulation results have shown that using cavitation model to analyze blade channel vortex is very effective [3]. A 2D numerical simulations of blade-vortex interaction in a darrieus turbine is given for instance by Amet E. et al [4], and the results are compared qualitatively with the visualization of the vortex shedding of Brochier. The occurrence of the blade channel vortex between the turbine runner blades is discussed depending on the mechanism calculation, and the frequency of vortex cavity is analyzed form Chen jinxia et al [5] 2.…”
Section: Introductionmentioning
confidence: 99%
“…The periodic nature of the flow past the blades is due to the cyclic variation (every rotor revolution) of modulus and direction of the relative velocity perceived by their airfoils [4], and also the interactions between the blades traveling in the downwind region of the rotor and the vorticity shed by the blades in the upwind rotor region [5]. These complex 125 unsteady flow patterns are further complicated by the occurrence of dynamic stall [6] over a significant portion of the entire turbine operating range [5].…”
mentioning
confidence: 99%
“…The report shows that the agreement between NS CFD analysis and measured data is substantially better than that between low-fidelity analyses and measured data, as expected. Early assessments of the NS CFD technology for Darrieus rotor aerodynamics, aiming primarily at thoroughly investigating the complex fluid mechanics of these machines, include the articles [16,5,6].…”
mentioning
confidence: 99%